2016
DOI: 10.33140/ijp/01/01/00003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Drug Abuse among Students of Tertiary Institutions in Abeokuta, Ogun State, Nigeria

Abstract: Background: In recent time, there has been a rise in the use of alcohol and psychoactive substances and the associated consequences among Nigerian students in tertiary institutions. Despite being a major public health concern, there are few studies that examined prevalence of alcohol and drug use among students of different tertiary institutions at the same point in time. Method: The self-administered WHO Student Drug Use Questionnaire was used to collect data on drug use among 1233 college students from the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
0
1
Order By: Relevance
“…Although this national survey did not survey for alcohol and tobacco use. In contrast, the past one-year prevalence of drug use among university students in the southwestern part of the country was higher (22.6%) than our result (13). Differences in socio-cultural characteristics of the people, and the different numbers of drugs included could be responsible for the observed differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although this national survey did not survey for alcohol and tobacco use. In contrast, the past one-year prevalence of drug use among university students in the southwestern part of the country was higher (22.6%) than our result (13). Differences in socio-cultural characteristics of the people, and the different numbers of drugs included could be responsible for the observed differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Male students were more likely to use drugs compare to their female counterparts. This result is consistent with the finding previous Nigerian and Sudanese drug use studies which reported the same sexbased differences in drug use (6,13,16,21). This finding may be due to male trait and show of power often exhibited by male students which may encourage drug use.…”
Section: Discussionsupporting
confidence: 92%